Psychobiotic supplementation of HK-PS23 improves anxiety in highly stressed clinical nurses: a double-blind randomized placebo-controlled study. Issue 17 (4th August 2022) - Wu, Shu-I; Wu, Chien-Chen; Cheng, Li-Hao; Noble, Samuel W.; Liu, Chih-Ju; Lee, Yu-Hsia; Lin, Chen-Ju; Hsu, Chih-Chieh; Chen, Wan-Lin; Tsai, Pei-Joung; Kuo, Po-Hsiu; Tsai, Ying-Chieh
Abstract : HK-PS23 demonstrated potential benefits in reducing the level of cortisol compared to placebo and might improve perceived anxiety states in nurses under particularly high levels of anxiety. Abstract : Nurses often experience adverse health effects associated with increasing levels of work-related stress. Stress may induce systemic effects through the HPA axis, glucocorticoid responses, and inflammatory cascades. Psychobiotics may help alleviate stress through associations of the microbiota, anti-inflammation factors, and the gut-brain axis. We aimed to investigate whether interventions with a psychobiotic, heat-killed (HK)-PS23 cells, may help improve perceived stress, anxiety, and related biological markers among highly stressed clinical nurses. This double-blind, randomized, placebo-controlled study included seventy clinical nurses from a medical center in Northern Taiwan who scored 27 or higher on the 10-item version of the Perceived Stress Scale (PSS), and participants were randomized into either taking HK-PS23 or a placebo for 8 weeks. Baseline and endpoint results of the PSS, Job Stress Scale, State and Trait Anxiety Index (STAI), emotional questionnaires, gastrointestinal severity questionnaires, Trails Marking Tests, blood biological markers, and sleep data were analyzed. While both groups demonstrated improvements in most measures over time, only the blood cortisol measure demonstrated significant group differences after the 8-week trial. Further analyses of the subgroup with higher anxiety (nurses with STAI ≥ 103) revealed that anxiety states had improved significantly in the HK-PS23 group but not in the placebo group. In summary, this placebo-controlled trial found significant reduction in the level of blood cortisol after 8 weeks of HK-PS23 use. The distinctive anxiolytic effects of HK-PS23 may be beneficial in improving perceived anxiety and stress hormone levels in female nurses under pressure. Clinical trial registration: https://clinicaltrials.gov/, identifier: NCT04452253-sub-project 1.